Massive ascariasis complicated by acute suppurative mediastinitis: a case report - Avalos-García, Roxana; Kindelán-Fortuné , Elizabeth; Iglesias-Serrano , Yilian Lázara; Hernández-Fernández , Diana Maité (Revista Científica Estudiantil de Ciencias Médicas de Matanzas, 2026)
Introduction: Massive ascariasis complicated by acute suppurative mediastinitis constitutes an exceptionally rare and lethal clinical presentation, not previously reported in the Cuban medical literature. Ascaris lumbricoides may migrate aberrantly toward the oropharynx, triggering catastrophic systemic complications in vulnerable patients. Objective: To report a case of massive ascariasis with acute suppurative mediastinitis in an adult with intellectual disability, emphasizing diagnostic difficulties and determinants of the fatal outcome. Case Presentation: A 56-year-old male patient with severe intellectual disability, schizophrenia, and homeless condition was admitted due to acute dysphagia. Initially, esophageal foreign body was suspected, but endoscopy revealed purulent nasopharyngeal secretions. Within 24 hours, he developed fever, left cervical swelling with crepitus, and expulsion of more than 16 worms through the oral route. Massive ascariasis was confirmed with absence of eosinophilia. Despite treatment with albendazol, ceftriaxone, and metronidazole, he died suddenly from cardiorespiratory arrest on day seven. Autopsy revealed massive gastrointestinal infestation, acute suppurative mediastinitis with infiltration of trachea and epiglottis, tracheitis, and multifocal bronchopneumonia. Conclusions: Massive ascariasis may evolve catastrophically through aberrant migration toward the oropharynx, triggering fatal descending necrotizing mediastinitis in patients with delayed diagnosis and vulnerability factors. Absence of eosinophilia and empirical corticosteroid use may mask infection severity. Community prevention, screening in psychiatric institutions, and timely clinical suspicion in at-risk populations constitute essential strategies to prevent fatal outcomes from this preventable parasitosis.